PENINGKATAN PERTUMBUHAN DAN PRODUKSI KEDELAI MELALUI KOMBINASI PUPUK ORGANIK LAMTOROGUNG DENGAN PUPUK KANDANG - Efendi Efendi (Jurnal Floratek, 2010)
Response of plant on agroinputs such as organic fertilizer is different, depending on cultivar. Nutrient composition of organic fertilizer is also varied from one to another. The cultivar of Kipas Putih and Anjasmara were studied. The growth and yield of soybean were significantly affected by cultivar and organic fertilizer,  composted from manure and green manure using EM-4.  The growth and yield of Kipas Putih were significantly better than those of Anjasmara.  Fertilization with 12.5 ton/ha of organic matter also increased growth and yield of soybean.